The power of patient‐led global collaboration. Issue 4 (6th November 2021) - Bloom, Lara; Schubart, Jane; Bascom, Rebecca; Hakim, Alan; Francomano, Clair A.
Abstract: In late 2017, the global nonprofit, The Ehlers‐Danlos Society (TEDS), was awarded a "Pipeline to Proposal" Tier A award from the Patient‐Centered Outcomes Research Institute (PCORI). The goal of this application was to form a team of patients, researchers, other community support groups and stakeholders who are focused on establishing the Ehlers‐Danlos Comorbidity Coalition to address the common health issues associated with this group of high morbidity, high disease burden conditions. The ongoing Coalition that is now funded by individual donors and expanding in its mission and members, is an example of successful collaboration spanning over borders and priorities.